Through the Haze: Evaluating the Effectiveness of Anti-Smoking Legislation in Australia in the 2000s - Jastrzab, J (My University, 2014)
I use natural experiment methodologies to evaluate whether smoke-free laws introduced in Australia in the 2000s affected smoking behaviour. Pictorial health warnings on cigarette packets led to a decrease of between 5.5% and 6.9% in smoking participation when introduced in 2006. Decreases of between 3.2% and 4.4% in smoking participation were found from territorial restrictions on enclosed public spaces such as pubs and restaurants, upon their full implementation between 2006 and 2008. These latter effects are driven by states that had a shorter period of restriction implementation, and more drastic law changes. The decreases in smoking participation were driven by decreases of 23.69% for moderate and 16.77% for light smokers, when breaking the effect down by state and type of smoker. The low predicted decreases in average cigarette consumption are reconciled by predicted decreases of up to 23.8% in consumption for moderate smokers, and up to a 33.1% decrease for light smokers, showing that such legislative changes were most effective on casual or social smokers.
Keywords: Health -- Addictive behaviours; Location -- Policy,Public economics; Government, law and policy; Health and wellbeing; Location; Health; Addictive behaviours; Policy,Public economics; Health and wellbeing; Government, law and policy